2013
DOI: 10.1371/journal.pone.0060935
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Paths of the cAMP-Dependent Protein Kinase (PKA) Catalytic Subunits

Abstract: 3′,5′-cyclic adenosine monophosphate (cAMP) dependent protein kinase or protein kinase A (PKA) has served as a prototype for the large family of protein kinases that are crucially important for signal transduction in eukaryotic cells. The PKA catalytic subunits Cα and Cβ, encoded by the two genes PRKACA and PRKACB, respectively, are among the best understood and characterized human kinases. Here we have studied the evolution of this gene family in chordates, arthropods, mollusks and other animals employing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 87 publications
(94 reference statements)
2
54
0
Order By: Relevance
“…C. elegans KIN-1 and KIN-2 show high protein sequence homology with mammalian PKA catalytic (ϳ80%) and regulatory (ϳ60%) subunit proteins. Multiple alignment and phylogram analysis showed that the isoforms of vertebrate PKA subunits would be diverged from ancestral forms as suggested previously (40). Thus, it appears that C. elegans PKA genes may have preserved ancestral forms of PKA and may be representative of many PKA genes among eukaryotes.…”
Section: Pka Subunit Stoichiometrysupporting
confidence: 63%
“…C. elegans KIN-1 and KIN-2 show high protein sequence homology with mammalian PKA catalytic (ϳ80%) and regulatory (ϳ60%) subunit proteins. Multiple alignment and phylogram analysis showed that the isoforms of vertebrate PKA subunits would be diverged from ancestral forms as suggested previously (40). Thus, it appears that C. elegans PKA genes may have preserved ancestral forms of PKA and may be representative of many PKA genes among eukaryotes.…”
Section: Pka Subunit Stoichiometrysupporting
confidence: 63%
“…They have the same length and share 93% sequence identity (Soberg et al ., 2013). To confirm the O‐GlcNAcylation of PKAcs, we overexpressed PKAcα (PKAcα1) or PKAcβ (PKAcβ1) tagged with HA at the N‐terminal in HEK‐293FT cells and immunoprecipitated them with monoclonal anti‐HA.…”
Section: Resultsmentioning
confidence: 99%
“…PKA-Cα expression was measured due to its highest expression in brain tissues (Soberg et al, 2013, Uhler et al, 1986. Therefore, two antibodies for PKA subunits were chosen in the present study: anti-PKA-Cα (1:1000; Santa Cruz, #SC-903) and anti-phosphor-PKA-C (Thr197) (1:1000; Cell Signalling, #5661).…”
Section: Western Blotsmentioning
confidence: 99%